Phenotype delineation of ZNF462 related syndrome. Issue 10 (30th July 2019) - Kruszka, Paul; Hu, Tommy; Hong, Sungkook; Signer, Rebecca; Cogné, Benjamin; Isidor, Betrand; Mazzola, Sarah E.; Giltay, Jacques C.; van Gassen, Koen L. I.; England, Eleina M.; Pais, Lynn; Ockeloen, Charlotte W.; et al.
Abstract: Zinc finger protein 462 (ZNF462) is a relatively newly discovered vertebrate specific protein with known critical roles in embryonic development in animal models. Two case reports and a case series study have described the phenotype of 10 individuals with ZNF462 loss of function variants. Herein, we present 14 new individuals with loss of function variants to the previous studies to delineate the syndrome of loss of function in ZNF46 2. Collectively, these 24 individuals present with recurring phenotypes that define a multiple congenital anomaly syndrome. Most have some form of developmental delay (79%) and a minority has autism spectrum disorder (33%). Characteristic facial features include ptosis (83%), down slanting palpebral fissures (58%), exaggerated Cupid's bow/wide philtrum (54%), and arched eyebrows (50%). Metopic ridging or craniosynostosis was found in a third of study participants and feeding problems in half. Other phenotype characteristics include dysgenesis of the corpus callosum in 25% of individuals, hypotonia in half, and structural heart defects in 21%. Using facial analysis technology, a computer algorithm applying deep learning was able to accurately differentiate individuals with ZNF462 loss of function variants from individuals with Noonan syndrome and healthy controls. In summary, we describe a multiple congenital anomaly syndrome associated with haploinsufficiency of ZNF462 that has distinct clinical characteristics and facial features.